Ankerius aenigmaticus, a new genus and new species of aphanodactylid crab symbiotic with polychaetes from the Red Sea coast of Saudi Arabia (Crustacea: Decapoda: Brachyura: Aphanodactylidae) - Ng, Peter K. L.; Rahayu, Dwi Listyo; Shih, Hsi-Te (Zootaxa, 2016)
A new genus and new species of pinnotheroid crab of the family Aphanodactylidae, Ankerius aenigmaticus n. sp., is described from the Red Sea coast of Saudi Arabia. The genus is unusual among aphanodactylids in possessing more gaping third maxillipeds, strongly spiniform chelipeds and ambulatory legs, as well as a relatively longer ambulatory dactylus.